Prevalence premature rupture of membranes in pregnant women with a history of anemia - Putri Amartya Dewanti; Fadil Hidayat (Science Midwifery, 2023)
Premature rupture of membranes is one of many obstetric problems that is dangerous for a mother in maternity. It is one of the top five reasons behind child mortality in the world and also one of the cause of premature labor. Premature rupture of membranes could be caused by anemia through many pathological mechanism. This research was conducted to determine the prevalence of premature rupture of membranes in pregnancy of anemic mothers in RSUD Kota Tangerang on 2018 – 2020. This research is descriptive research with cross-sectional design. Data retrieval was carried out in RSUD Kota Tangerang throughout January – May 2022 with medical records instrument. Samples were retrieved using non-random sampling method. Based on the research results, a total of 75 samples of pregnant women with anemia was collected. The result showed a total of 38 samples (50.7%) pregnant women with anemia experienced premature rupture of membrane. In addition, as many as 37 samples (49.3%) of pregnant women with a history of anemia who did not experience premature rupture of membranes. It can be concluded the prevalence of premature rupture of membranes in pregnant anemic woman is more than those who did not experience premature rupture of membranes in RSUD Kota Tangerang.